Affinity of sulfamates and sulfamides to carbonic anhydrase II isoform: Experimental and molecular modeling approaches - Gavernet, Luciana (2010)
Sixteen aromatic and aliphatic sulfamides and sulfamates were synthesized and tested in their inhibition to carbonic anhydrase CAII activity. The weaker inhibition pattern shown by sulfamides as compared to sulfamates is interpreted in this research by means of molecular modeling techniques, including known inhibitors (topiramate and its sulfamide cognate) in the analysis. The results nicely explain the origin of the inhibitory activity, which is not only related to positive interactions of the ligand with the active site residues but also to the solvation pattern characteristic of each ligand.